The penalty is death : U.S. newspaper coverage of women's executions - Shipman, Marlin (University of Missouri Press, 2002)
"In "The Penalty Is Death," Marlin Shipman examines the shifts in press coverage of women's executions over the past one hundred and fifty years. Since the colonies' first execution of a woman in 1632, about 560 more women have had to face the death penalty. Newspaper responses to these executions have ranged from massive national coverage to limited regional and even local coverage. Throughout the years the press has been guilty of sensationalism, stereotyping, and marginalizing of female convicts, making prejudicial remarks, trying these women in the media, and virtually ignoring or simply demeaning African American women convicts. This researched book studies countless episodes that serve to illustrate these points."--Jacket.